ENGLISH FOR ACADEMIC PURPOSES AS A KEY COMPONENT OF PHILOLOGY STUDENTS TRAINING - Tymoshchuk, Nataliia (Collection of scientific papers «ΛΌГOΣ», 2025)
This article explores the role of the English for Academic Purposes course as a key component in training master’s students in philology. It presents evidence from implementing the Vinnytsia Institute of Trade and Economics course, highlighting its positive impact on students’ academic writing, research skills, and overall academic performance. The study emphasizes the importance of discipline-specific instruction and integrated teaching approaches. The findings confirm that EAP significantly contributes to developing students’ scholarly competencies and prepares them for academic and professional communication in an international context.